Analisis Pengaruh Customer Experience dan E-Service Quality terhadap Customer Satisfaction pada Pengguna Transportasi Online di Jakarta - Nur Faizi; Ika Febrilia; Rahmi (Jurnal Bisnis, Manajemen, dan Keuangan, 2022)
This study aims to examine the effect of customer experience and e-service quality on customer satisfaction of online transportation users in Jakarta. Data were collected by applying the purposive sampling method using a Likert scale. The samples collected were 200 respondents with the criteria of UNJ economics faculty students who had used Gojek in Jakarta at least twice. The researcher collected the data with a questionnaire Liker scale of 1-5. The data were processed using SPSS version 25 software to test their validity and reliability. Data analysis testing using Amos software version 21. Based on the data that has been collected and analyzed, there is an influence between customer experience on customer satisfaction, e-service quality on customer satisfaction, as well as customer experience and e-service quality. to customer satisfaction. This study aims to examine the effect of customer experience and e-service quality on customer satisfaction of online transportation users in Jakarta. Data were collected by applying the purposive sampling method using a Likert scale. The samples collected were 200 respondents with the criteria of UNJ economics faculty students who had used Gojek in Jakarta at least twice. The researcher collected the data with a questionnaire Liker scale of 1-5. The data were processed using SPSS version 25 software to test their validity and reliability. Data analysis testing using Amos software version 21. Based on the data that has been collected and analyzed, there is an influence between customer experience on customer satisfaction, e-service quality on customer satisfaction, as well as customer experience and e-service quality. to customer satisfaction.